Both glypican-3/Wnt/β-catenin signaling pathway and autophagy contributed to the inhibitory effect of curcumin on hepatocellular carcinoma. Issue 1 (January 2019) - Hu, Pei; Ke, Changzheng; Guo, Xingrong; Ren, Pan; Tong, Yaoyao; Luo, Sen; He, Yulin; Wei, Zhiqiang; Cheng, Bin; Li, Ruiming; Luo, Jie; Meng, Zhongji
Abstract: Aim: The aim of this study is to investigate the role of glypican-3(GPC3)/wnt/β-catenin signaling pathway and autophagy in the regulation of hepatocellular carcinoma (HCC) growth mediated by curcumin. Methods: HepG2 cells were treated with various concentrations of curcumin and/or GPC3-targeting siRNA in the presence or absence of 3-MA. Cell proliferation and apoptosis were determined by MTT and TUNEL assay, respectively. Expression of GPC3, β-catenin, c-myc, LC3, and Beclin1 was determined by western blotting. In addition, curcumin was tested in tumor xenografts mice model, Caliper IVIS Lumina II was used to monitor the tumor growth, and GPC3/wnt/β-catenin signaling proteins were determined by western blotting. Results: Curcumin treatment led to proliferation inhibition and apoptosis induction in HepG2 cells in a concentration-dependent manner, and suppressed HCC tumor growth in vivo. Further analysis showed that curcumin treatment inactivated Wnt/β-catenin signaling and decreased GPC3 expression, silencing of GPC3 expression promoted the effects of curcumin on Wnt/β-catenin signaling. In addition, inhibiting autophagy by 3-MA relieved curcumin-dependent down-regulation of GPC3. Conclusion: Curcumin suppressed HCC tumor growth through down-regulating GPC3/wnt/β-catenin signaling pathway, which was partially mediated by activation of autophagy.